PENDIDIKAN AGAMA ISLAM DALAM KELUARGA SEBAGAI STRATEGI PENDIDIKAN ANAK USIA DINI SAAT PANDEMI COVID-19 - Wachyudi Achmad (JCE (Journal of Childhood Education), 2020)
Islamic religious education in the family is now a perfect strategy to continue to provide early childhood rights in the form of education and teaching of the values as well as the role of religion in the life that a child will go through. The role of parents is now being tested with the Covid-19 pandemic that has hit this country. Many things must also be considered in providing education, especially Islamic religious education in the family, namely habituation factors and also assistance in following worship rituals, the need for the importance of applying Islamic character, and also those related to psychology, the comfort of early childhood when learning education religion and play at home. Through a qualitative case study approach with ten parents with a master's education background and academic professions became respondents through questionnaires and digital interviews with the Google Form application. The results of the questionnaires and interviews were analyzed by means of descriptive analysis. It was found that: (1) only three out of ten parents can adapt to their role as educators for their own children and are able to create comfort when providing learning to children at home; (2) three in ten parents are able to establish good communication with teachers during educational activities from home; (3) the ten parents expressed their concern with the existing conditions and agreed that the role of the teacher was not easy to fulfill.